2015 update on the diagnosis and management of arrhythmogenic right ventricular cardiomyopathy. (January 2016) - Philips, Binu; Cheng, Alan
Abstract : Purpose of review: This review will discuss the recent advances in the diagnosis and management of arrhythmogenic right ventricular cardiomyopathy (ARVC). Recent findings: Since the first detailed clinical description of the disease in 1982, we have learned much about the genetics, pathophysiology, diagnosis, and management of ARVC. We now appreciate that pathogenic mutations in desmosomal genes are the most common genetic finding. Although the right ventricle is mostly affected, left ventricular involvement is being increasingly recognized. Electrical instability precipitating sudden cardiac death often presents before structural abnormalities, and therefore early accurate diagnosis is of utmost importance. The broad spectrum of phenotypic variation, age-related penetrance, and lack of a definitive diagnostic test make the clinical diagnosis challenging. The diagnosis is made by fulfilling the 2010 Task Force criteria. Today, genetic testing and cardiac MRI play an important role in the diagnosis. Implantable cardioverter defibrillator implantation is the only lifesaving therapy available today for a subset of patients. In patients with recurrent ventricular arrhythmias, epicardial catheter ablation has demonstrated improved outcomes compared with endocardial ablation. Exercise restriction may delay the progression of disease. Summary: ARVC is predominantly associated with mutations in desmosomal genes with incomplete penetrance and variable expressivity. Ventricular electrical instability is the hallmark of ARVC, often occurring before structural abnormalities. Goals in the evaluation and management of ARVC are early diagnosis, risk stratification for sudden cardiac death, minimizing ventricular arrhythmias, and delaying the progression of disease.